PENGARUH PENDAPATAN USAHA DAN BIAYA OPERASIONAL TERHADAP LABA BERSIH PADA DEPOT AIR RADEN WATER MEDAN - Kronica Pitaloka Siagian, Sheylina; Epi, Yus; S.SE,MM, Yanti (Jurnal Manajemen Dan Akuntansi Medan, 2025)
Profit is a benchmark in every business action to evaluate achievable goals. To earn profit, business income and operating costs are very important factors because they are very helpful in measuring the company's expected costs to earn profits. This study was conducted to determine the effect of business income and operating costs on net profit at Depot Air Raden Water Medan. The data collection method used in this study was interviews. The researcher also conducted a literature study, which is a research method that involves reading reference materials relevant to the problem and other research results related to the object being studied. The data analysis method used was descriptive analysis because it collected data containing several descriptions of the object being studied. In this study, Raden Water Depot Medan kept simple records of income and operational costs. The records only included daily sales without regularly summarizing income. For operational costs, the funds spent were also not recorded in detail. As a result, the financial reports presented did not show the actual results. Based on the discussion provided, it can be concluded that revenue affects profit. The revenue generated by Raden Water Depot Medan has been decreasing monthly, and operational expenses vary. To increase profit, Raden Water Depot Medan must increase water sales and improve service quality in handling customers.